Evolutionary computation in combinatorial optimization : 17th European Conference, EvoCOP 2017, Amsterdam, the Netherlands, April 19-21, 2017, Proceedings /: 17th European Conference, EvoCOP 2017, Amsterdam, the Netherlands, April 19-21, 2017, Proceedings. (2017) - Unknown
No abstract available